2014
DOI: 10.1007/s10826-014-9913-8
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian and Heterosexual Two-Parent Families: Adolescent–Parent Relationship Quality and Adolescent Well-Being

Abstract: This study compared 51 adolescents from intact two-mother planned lesbian families (all conceived through donor insemination) with 51 adolescents from intact motherfather families on their relationships with their parents (parental control, disclosure to parents, and adolescentparent relationship quality), psychological adjustment (selfesteem, social anxiety, and conduct problems), and substance usage (consumption of tobacco, alcohol, and marijuana/hashish). The adolescents (average age 16 years) were matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…13 The observed similarity in child outcomes by household type is also consistent with numerous studies of lesbian- and gay-parent families using convenience- and/or fertility clinic-based samples, 2,57 although the convenience-based U.S. National Longitudinal Lesbian Family Study (NLLFS) found that adolescents reared by lesbian mothers demonstrated more competencies and fewer behavioral problems than the normative sample of same-age youth, 4 and the Dutch Longitudinal Lesbian Family Study that adolescent offspring of lesbian mothers had higher self-esteem than peers in different-sex parent families. 27 The current study contributes to the mounting evidence that children reared by same-sex parents fare at least as well as those reared by different-sex parents on a variety of measures used to assess psychological adjustment. 2,6,8…”
Section: Discussionmentioning
confidence: 86%
“…13 The observed similarity in child outcomes by household type is also consistent with numerous studies of lesbian- and gay-parent families using convenience- and/or fertility clinic-based samples, 2,57 although the convenience-based U.S. National Longitudinal Lesbian Family Study (NLLFS) found that adolescents reared by lesbian mothers demonstrated more competencies and fewer behavioral problems than the normative sample of same-age youth, 4 and the Dutch Longitudinal Lesbian Family Study that adolescent offspring of lesbian mothers had higher self-esteem than peers in different-sex parent families. 27 The current study contributes to the mounting evidence that children reared by same-sex parents fare at least as well as those reared by different-sex parents on a variety of measures used to assess psychological adjustment. 2,6,8…”
Section: Discussionmentioning
confidence: 86%
“…These studies showed that children born into such families had comparable well‐being to that of children born into different‐sex parent households (for overview, see Goldberg, ). Some studies found that when compared to those reared in different‐sex parent families, adolescents raised since birth in female same‐sex parent households had higher levels of self‐esteem and less externalizing problem behavior (Bos, Van Gelderen, & Gartrell, ; Gartrell & Bos, ).…”
Section: Planned Same‐sex Parent Family Studies Using Nonprobability mentioning
confidence: 99%
“…These studies evaluate the adequacy of children's development and the quality of parenting using psychological tests, psychometric techniques and standardised interviews and questionnaires. Findings from this research show that same‐sex parenting is not associated with deficits in cognitive and social adjustment, disruptions in the development of sexual orientation and identity or in the quality of parenting (Bos and others, ; Golombok and Badger, ; Tasker, ). Moreover, some research finds that children with two mothers enact less gender‐stereotyped behaviours, attitudes and preferences; enjoy greater emotional well‐being; and show fewer social and behavioural problems than their peers who have grown up in heterosexual parent families (Anderssen and others, ; Bos and Sandfort, ; Gartrell and others, ).…”
Section: Introductionmentioning
confidence: 86%